2016
DOI: 10.1590/1679-78252458
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Shaper and Dynamic Compressive Property Investigation on Ice Using a Large-Sized Modified Split Hopkinson Pressure Bar

Abstract: The dynamic compressive behavior of ice is investigated using a large-sized (37 mm in diameter) modified aluminum split Hopkinson pressure bar (SHPB) with pulse shaper at the strain rate from 500 s -1 to 1200 s -1 . A series of relatively stable experimental results of dynamic compressive strength versus strain rate and a linear fitting curve have been obtained by controlling data scatter within 25%. The composition of incident wave has been discussed. The effects of pulse shaper diameter and velocity of strik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 30 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…However, the transmission signal of soft biological materials is very weak. To solve this problem, the transmitted bar is a hollow rod with an inner diameter of 18 mm [21,22]. The striker bar is connected to a pneumatic cylinder, and its movement generates a collision between the striker and incident bars.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the transmission signal of soft biological materials is very weak. To solve this problem, the transmitted bar is a hollow rod with an inner diameter of 18 mm [21,22]. The striker bar is connected to a pneumatic cylinder, and its movement generates a collision between the striker and incident bars.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a hollow transmitted bar solved the problem that the waves on the transmitted bar were too weak as mentioned above. The transmitted pulse passing through the hollow bar created an ampli ed strain signal, which the sensors could measure easily [21,22]. It was noted that, unliked experiments at quasi-static strain rate, the recorded strain ranges were smaller.…”
Section: Methodsmentioning
confidence: 99%
“…One way of achieving this is to increase the rise time of the loading pulse by placing a piece of copper shim on the impact end of the input bar ( Fig. 8) [24,25,[74][75][76][77]. We used colloidal graphite lubricant paste to attach the shim to the bar end.…”
Section: Split Hopkinson Pressure Barmentioning
confidence: 99%
“…Bagher Shemirani et al [23] have studied the effects of parameters, such as striker bar velocity and diameter and pulse shaper thickness, on the incident wave and concluded that a small diameter and thick pulse shaper is proper for concrete tests. Song et al [24] have stated that the thickness of a pulse shaper was proportional to the pulse wave rising time.…”
Section: Introductionmentioning
confidence: 99%